A Nonlinear Multicriteria Model for Team Effectiveness - Dimas, Isabel Dórdio (2016)
The study of team effectiveness has received significant attention in recent years. Team effectiveness is an important subject since teams play an increasingly decisive role on modern organizations. This study is inherently a multicriteria problem as different criteria are typically required to assess team effectiveness. Among the different aspects of interest on the study of team effectiveness one of the utmost importance is to acknowledge, as accurately as possible, the relationships that team resources and team processes establish with team effectiveness. Typically, these relationships are studied using linear models which fail to explain the complexity inherent to group phenomena. In this study we propose a novel approach using radial basis functions to construct a multicriteria nonlinear model to more accurately capture the relationships between the team resources/processes and team effectiveness. By combining principal component analysis, radial basis functions interpolation, and cross-validation for model parameter tuning, we obtained a data fitting method that generated an approximate response with reliable trend predictions between the given data points.